Isokinetic Strength of Rotators, Flexors and Hip Extensors is Strongly Related to Front Kick Dynamics in Military Professionals - Vagner, Michal; Malecek, Jan; Tomšovský, Luboš; Kubový, Petr; Levitova, Andrea; Stastny, Petr (Journal of human kinetics, 2019)
Achieving the maximum possible impact force of the front kick can be related to the isokinetic lower limb muscle strength. Therefore, we aimed to determine the regression model between kicking performance and the isokinetic peak net moment of hip rotators, flexors, and hip extensors and flexors at various speeds of contraction. Twenty-five male soldiers (27.7 ± 7.2 yrs, 83.8 ± 6.1 kg, 180.5 ± 6.5 cm) performed six barefoot front kicks, where impact forces (N) and kick velocity (m∙s-1) were measured. The 3D kinematics and isokinetic dynamometry were used to estimate the kick velocity, isokinetic moment of kicking lower limb hip flexors and extensors (60, 120, 240, 300°∙s-1), and stance lower limb hip internal and external rotators (30, 90°∙s-1). Multiple regression showed that a separate component of the peak moment concentric hip flexion and extension of the kicking lower limb at 90°∙s-1 can explain 54% of the peak kicking impact force variance (R2 = 0.54; p < 0.001). When adding the other 3 components of eccentric and concentric hip internal and external rotations at 30°∙s-1, the internal and external hip rotation ratios at 30°∙s-1 on the stance limb and the concentric ratio of kicking limb flexion and extension at 300°∙s-1 that explained the variance of impact force were 75% (p = 0.003). The explosive strength of kicking limb hip flexors and extensors is the main condition constraint for kicking performance. The maximum strength of stance limb internal and external rotators and speed strength of kicking limb hip flexors and extensors are important constraints of kicking performance that should be considered to improve the front kick efficiency.
Keywords: peak moment; strike; impact force; self-defense; resistance training